Literature Review: Pengaruh Sosial Media dan Body Shaming Terhadap Gangguan Makan Remaja - Gusti Ayu Rivanya Pratistitha (Media Gizi Kesmas, 2023)
Background: Many teenagers use social media applications because of the many interesting features that are entertaining and effective for communicating. But unfortunately, social media is often used to carry out negative actions by teenagers, such as cyberbullying. There are so many types of cyberbullying that can be done by teenagers, one of which is body shaming. Some teenagers who receive body shaming comments on their social media, experience psychological effects such as eating disorders. Eating disorder behaviors that arise as a result of body shaming often appear in adolescents. Objectives: To see the effect between the use of social media and body shaming and eating disorders in adolescents. Methods: Review the literature on articles related to the topic with the keywords social media, body shaming, eating disorders and adolescents. Discussion: The results obtained from the 11 articles stated a significant relationship between social media and body shaming with the emergence of eating disorders in adolescents. Circulating content about appearance and coupled with celebrities or influencers on social media seems to instill the ideal body shape, namely a slim body. There are bad comments about their bodies, the more they want to have a slim and thin body. They are dissatisfied with their current body image so they go on a stricter diet, and eating disorders occur. Conclusions: Social media and body shaming are often the cause of eating disorders suffered by teenagers. The presence of comments or jokes about their body shape makes teenagers feel that having a slim body is more accepted in their social circle, and eating disorders arise.